2015
DOI: 10.1002/ijc.29468
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease in Adult Life after Childhood Cancer in Scandinavia: A population‐based cohort study of 32,308 one‐year survivors

Abstract: The lifetime risk for cardiovascular disease in a large cohort of childhood cancer survivors has not been fully assessed. In a retrospective population-based cohort study predicated on comprehensive national health registers, we identified a cohort of 32,308 one-year survivors of cancer diagnosed before the age of 20 in the five Nordic countries between the start of cancer registration in the 1940s and 1950s to 2008; 211,489 population comparison subjects were selected from national population registers. Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 32 publications
4
63
0
1
Order By: Relevance
“…In this procedure, the patient’s immune system is ablated by ionizing radiation or chemotherapy, which, as an unwanted side effect, creates a senescent cell–rich milieu that might not only impair the engraftment and functionality of the hematopoietic system of the healthy donor 141,142 , but also accelerate tissue deterioration at a systemic level. Consistent with this, survivors of pediatric cancer who have gone through such treatments exhibit signs of premature aging 143 , including loss of cognitive function 144 and heart failure 145 , with precocious elevation of p16 Ink4a in skin 49 .…”
Section: Therapy-induced Senescencementioning
confidence: 67%
“…In this procedure, the patient’s immune system is ablated by ionizing radiation or chemotherapy, which, as an unwanted side effect, creates a senescent cell–rich milieu that might not only impair the engraftment and functionality of the hematopoietic system of the healthy donor 141,142 , but also accelerate tissue deterioration at a systemic level. Consistent with this, survivors of pediatric cancer who have gone through such treatments exhibit signs of premature aging 143 , including loss of cognitive function 144 and heart failure 145 , with precocious elevation of p16 Ink4a in skin 49 .…”
Section: Therapy-induced Senescencementioning
confidence: 67%
“…Z największym łącznym ryzykiem CVD wiązało się leczenie raka wą-troby, chłoniaka Hodgkina i białaczek, a najczęstszymi problemami były kolejno: HF [ryzyko względne (RR) 5,2; 95% przedział ufności (CI) 4,5-5,9], dysfunkcja zastawki (RR 4,6; 95% CI 3,8-5,5) oraz choroba naczyniowo-mó-zgowa (RR 3,7; 95% CI 3,4-4,1). W porównaniu z grupą kontrolną ryzyko dowolnej CVD wykazywało znaczną zmienność, z prawie 20-krotnym wzrostem ryzyka wśród młodych pacjentów w porównaniu z ryzykiem względnym wynoszącym zaledwie 1,3 wśród osób po przebytym nowotworze w wieku > 60 lat, co wynika z następującego wraz z wiekiem znacznego wzrostu zapadalności na CVD niezwiązanego z nowotworem [217]. W ostatnio opublikowanych ujednoliconych międzynarodowych wytycznych zalecono dożywotnią obserwację pacjentów po przebytym leczeniu przeciwnowotworowym w dzieciństwie, u których stosowano antracykliny, radioterapię z użyciem dużych dawek obejmujących klatkę piersiową lub obie te metody terapii [91,92].…”
Section: Populacja Pediatrycznaunclassified
“…This increase in risk is seen throughout the follow-up. 5,6 Notably, we show that the increase in risk for CVD among survivors was higher the first 15 years after the cancer diagnosis, although it was still almost 2-fold after 15 or more years. In this cohort, 1-year survivors had a 1.7 times increased risk of diabetes in comparison with the general population, and this is in accordance with earlier reports.…”
Section: Within-cohort Analysesmentioning
confidence: 72%
“…1 However, these advances in treatment and survival come at a price, and many survivors face an increased risk for a broad range of treatment-induced sequelae, most of which become clinically apparent many years after the children have been cured. [4][5][6][7][8] Previous research has also shown that childhood cancer survivors have an increased risk for diabetes mellitus. [4][5][6][7][8] Previous research has also shown that childhood cancer survivors have an increased risk for diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%